Magnetic fluid seal critical pressure calculation based on numerical simulations. (April 2020) - Szczęch, Marcin
Magnetic fluid seals are among the most common ferrofluid applications. One interesting area is the use of numerical simulations to determine the critical pressure, which is a basic parameter determining the possible range of seal operating pressures. The purpose of this study is to present the method of critical pressure calculations in magnetic fluid seals based on magnetic field numerical simulations, which will provide better results than the methods used previously. It is a relatively simple method and can help to reduce the difference between simulations and experiments. Different seal stage shapes, such as symmetric trapezoidal, asymmetric trapezoidal, and rectangular, were taken into account. The research shows that an increase in the magnetic fluid volume applied at the seal stage and a magnetic saturation increase in the seal gap allow the manufacturing inaccuracy influence to be reduced, meaning that the difference between the simulation and experiment results is smaller. In addition, in this paper, the pressure transfer mechanism between liquid rings of the multistage seal is analyzed to show its influence on the critical pressure value calculated based on simulations.